Preoperative Epoetin-α with Intravenous or Oral Iron for Major Orthopedic Surgery: A Randomized Controlled Trial. (October 2018) - Biboulet, Philippe; Bringuier, Sophie; Smilevitch, Pierre; Loupec, Thibault; Thuile, Caroline; Pencole, Mathieu; Maissiat, Guillaume; Dangelser, Gaëtan; Capdevila, Xavier
Editor's Perspective: What We Already Know about This Topic: Epoetin-α is often given to patients scheduled for major orthopedic surgery It remains unknown whether it is best to accompany epoetin-α with oral or intravenous iron What This Article Tells Us That Is New: Hemoglobin level the day before surgery was 1 g/dl greater in 50 patients randomized to intravenous iron than in those assigned to oral iron About half the patients given oral iron reported gastrointestinal symptoms Intravenous iron is preferable to oral iron as a supplement to epoetin-α Background: Preoperative administration of epoetin-α with iron is commonly used in anemic patients undergoing major orthopedic surgery, but the optimal route of iron intake is controversial. The aim of this study was to compare the clinical effects of erythropoietin in combination with oral or intravenous iron supplementation. Methods: This study was a prospective, randomized, single-blinded, parallel arm trial. Patients scheduled for elective hip or knee arthroplasty with hemoglobin 10 to 13 g/dl received preoperative injections of erythropoietin with oral ferrous sulfate or intravenous ferric carboxymaltose. The primary endpoint was the hemoglobin value the day before surgery. Results: One hundred patients were included in the analysis. The day before surgery, hemoglobin, increase in hemoglobin, and serum ferritin level were higher in the intravenous group. For the intravenous and oral groups, respectively, hemoglobin was as follows: median, 14.9 g/dl (interquartile range, 14.1 to 15.6) versus 13.9 g/dl (interquartile range, 13.2 to 15.1), group difference, 0.65 g/dl (95% CI, 0.1 to 1.2; P = 0.017); increase in hemoglobin: 2.6 g/dl (interquartile range, 2.1 to 3.2) versus 1.9 g/dl (interquartile range, 1.4 to 2.5), group difference, 0.7 g/dl (95% CI, 0.3 to 1.1; P < 0.001); serum ferritin: 325 µg/l (interquartile range, 217 to 476) versus 64.5 µg/l (interquartile range, 44 to 107), group difference, 257 µg/l (95% CI, 199 to 315; P < 0.001). The percentage of patients with nausea, diarrhea, or constipation was higher in the oral group, 52% versus 2%; group difference, 50% (95% CI, 35 to 64%; P < 0.0001). Conclusions: After preoperative administration of erythropoietin, body iron stores and stimulation of the erythropoiesis were greater with intravenous ferric carboxymaltose than with oral ferrous sulfate supplementation. Abstract : Hemoglobin concentration the day before surgery was 1 g/dl greater in 50 patients randomized to intravenous iron than in those assigned to oral iron. About half the patients given oral iron reported gastrointestinal symptoms. Intravenous iron is preferable to oral iron as a supplement to epoetin-α.